Flood Mitigation Infrastructure in Southeast Asia: A Comparative Study of Malaysia’s and Indonesia’s Approaches to Achieving the Sustainable Development Goals - Moh. Nizar; Astiwi Inayah; Noranida Mokthsim (Department of Government Studies, Faculty of Social and Political Sciences, Universitas Syiah Kuala, 2025)
Floods are the most common natural disasters in Indonesia and Malaysia, causing damage to property and infrastructure and disrupting the lives of millions of people every year. Indonesia experienced 11,501 flood events between 2015 and 2024, while Malaysia recorded 6,427 events during the same period. This study aims to examine flood mitigation approaches in Indonesia and Malaysia in achieving the Sustainable Development Goals (SDGs). The study uses a qualitative approach with descriptive analysis combined with the interactive model of Miles, Huberman, and Saldana. Primary data was obtained from interviews with disaster infrastructure experts from the University of Northern Malaysia, while secondary data came from policy documents, BNPB reports, and journal publications. The results of the study show that Indonesia and Malaysia apply an approach that combines structural and non-structural infrastructure in flood mitigation. An integrated framework through three pillars, namely structural and non-structural integration, technological innovation and local resources, and stakeholder involvement, is expected to strengthen the flood mitigation infrastructure of both countries